Numerical comparison of cruciform weld and butt weld simulation and a study of fracture mechanics on two types of welds - Malika Tirenifi; Bahri Ould Chikh; Benattou Bouchouicha; Ahmed Bensari (Fracture and Structural Integrity)
The modeling of the welding is desirable to guess the deformation of the components during manufacture, the position and the magnitude of maximum residual stresses and to envisage metallurgical effects in specific zones. The welding are problems of complex modeling requiring the thermal and structural solutions. This has to lead to the development of several software packages and codes for simulation by finite elements. The welding condition, the properties of the structure and their interactions have significant influences on the thermal and structural responses (temperature history, distortion, and residual stress) in welded structures. This paper presents a finite element procedure for the prediction of welding-induced residual stresses and distortions. Comparison is made with tow numerical example. The first example is a butt welded joint of two plates, while the second is a Cruciform welded joint of two plates with four passes. Moreover, a comparison between the Cruciform weld and the butt-weld which we can obtain the parameters of the linear fracture mechanics; stress intensity factor K and energy release rate G.